2021
DOI: 10.1111/rda.13901
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA‐seq reveals mRNAs and lncRNAs important for oocytes in vitro matured in pigs

Abstract: The faithful execution of molecular programme underlying oocyte maturation and meiosis is vital to generate competent haploid gametes for efficient mammalian reproduction. However, the organization and principle of molecular circuits and modules for oocyte meiosis remain obscure. Here, we employed the recently developed single‐cell RNA‐seq technique to profile the transcriptomes of germinal vesicle (GV) and metaphase II (MII) oocytes, aiming to discover the dynamic changes of mRNAs and long non‐coding RNAs (ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…At the translational level, it has been shown that miR-181c in concert with Ago2 can repress the translation of the mitochondrial cyclooxygenase ( Cox1 ) mRNA, determining a remodeling of complex IV in cardiac dysfunction ( 68 , 69 , 78 , 79 ). Noteworthy, Cox1 transcript is among the transcripts induced during oocyte maturation ( 80 ). Similarly, miR-378 can inhibit the mitochondrial expression of Atp6 ( 71 ) that modulates mouse follicle development and oocyte maturation as well as aromatase levels ( 70 ).…”
Section: Mitochondrion-nucleus Crosstalk: a Focus On Ncrnas Acting As Anterograde And Retrograde Signalsmentioning
confidence: 99%
“…At the translational level, it has been shown that miR-181c in concert with Ago2 can repress the translation of the mitochondrial cyclooxygenase ( Cox1 ) mRNA, determining a remodeling of complex IV in cardiac dysfunction ( 68 , 69 , 78 , 79 ). Noteworthy, Cox1 transcript is among the transcripts induced during oocyte maturation ( 80 ). Similarly, miR-378 can inhibit the mitochondrial expression of Atp6 ( 71 ) that modulates mouse follicle development and oocyte maturation as well as aromatase levels ( 70 ).…”
Section: Mitochondrion-nucleus Crosstalk: a Focus On Ncrnas Acting As Anterograde And Retrograde Signalsmentioning
confidence: 99%
“…Third, oocytes are surrounded by granulosa cells, making large-scale cell isolation challenging. Because of the aforementioned reasons, most of the current scRNA-seq studies focus on oocytes at GV, MI, and MII stages with limited cell numbers in each experiment, which makes it hard to compare male and female germ-cell transcriptomes at single-cell level (Ferrero et al, 2019;Zhang T. et al, 2019;Ye et al, 2020;Yu et al, 2020;Yang et al, 2021). It is not until recent years that scRNA-seq was applied to transcriptome studies of early prophase I oocytes (Li et al, 2017;Ge et al, 2020;Niu and Spradling, 2020;Wang et al, 2020).…”
Section: Comparing Meiotic Scrna-seq Studies Between Male and Femalementioning
confidence: 99%
“…oocytes, or comparing abnormal oocytes with normal oocytes at the MII stage (Zhang et al, 2018;Ferrero et al, 2019;Ye et al, 2020;Yang et al, 2021).…”
Section: How Can We Conduct Scrna-seq To Study Meiosis? What Sequencing Strategies To Choose For Meiosis Studies?mentioning
confidence: 99%
“…Single-cell RNA-seq raw data for three GV oocytes (GV1, GV2 and GV3) and three MII oocytes (MII1, MII2 and MII3) were downloaded from GSE16 0334 that we have previously deposited in NCBI GEO repository (http://www.ncbi.nlm.nih.gov/geo/; Yang et al, 2021).…”
Section: Acquisition and Processing Of Raw Datamentioning
confidence: 99%